Asymmetric Spacer in Dion–Jacobson Halide Perovskites Induces Staggered Alignment to Direct Out‐of‐Plane Carrier Transport and Enhances Ambient Stability Simultaneously. (12th August 2021) - Yu, Shuang; Abdellah, Mohamed; Pullerits, Tõnu; Zheng, Kaibo; Liang, Ziqi
Abstract: Dion–Jacobson (DJ)‐type 2D halide perovskites present superior environmental stability and a narrower bandgap, yet a contradiction between charge transport and stability remains to be resolved. Herein, it is shown that both symmetry and substitution of the organic spacer in DJ perovskites synergistically direct the narrow interlayer spacing, staggered spacer alignment, and regular phase arrangement, thereby promoting out‐of‐plane carrier transport and ambient stability. Compared to its symmetric para ‐xylylenediamine (PDMA) counterpart, the asymmetric 2‐(4‐aminophenyl)ethylamine (PMEA) spacer largely aids in compressing the inorganic octahedra layer to form a non‐confinement structure with decreased exciton binding energy, while stacked benzene rings enable a staggered alignment of spacers. Such non‐confined structures are less remarkable in meta ‐substituted diamine‐based DJ perovskites than those para ‐ones, which retard carrier transport from 2D to quasi‐2D phases. The preferential PMEA spacer however requires a long relaxation time to form a dense and ordered staggered alignment, which is realized by a slight addition of strong‐coordinating DMSO into the DMF solvent, thus decelerating crystallization and further optimizing lamellar orientation. As a result, a best efficiency of ≈ 12% is achieved in (PMEA)MA3 Pb4 I13 based p‐i‐n type planar solar cells. Importantly, such unencapsulated devices can maintain 81% initial efficiencies after storage in ambient conditions ( ≈ 60% relative humidity, ≈ 20 °C) for 700 h. Abstract : Para‐substituted asymmetric aromatic spacer structures in 2D Dion−Jacobson perovskites are proposed, in which the non‐confinement phase decreases exciton binding energy while staggered benzene rings expedite to form a dense and ordered alignment of spacer layers. As a result, the para ‐substituted spacers offer narrower quasi‐2D n ‐value distribution, giving rise to the high efficiency of ≈12% with excellent ambient stability in solar cells.